COMPARISON OF MEASLES COMPLICATIONS IN WELLNOURISHED AND MAL-NOURISHED CHILDREN - Qaisar, Imran; Ahmad, Ameer; Ahmad, Fiaz; Mazhar, Atta ullah (Journal of Ayub Medical College Abbottabad, 2009)
Background: Measles is the most common and the most infectious of the viral infections of childhood. It can cause severe pneumonia, diarrhoea, encephalitis, and death. A significant proportion of deaths due to measles in young children worldwide are attributable to low weight for age. To compare the measles complications in well-nourished and mal-nourished children, this cross-sectional study was conducted at Paediatric out-patient department and paediatric unit 1 Bahawal Victoria Hospital Bahawalpur. Methods: Total 120 patients were included in the study. All patients presented with signs and symptoms suggestive of measles according to WHO criteria. These patients were divided into wellnourished and malnourished according to the modified Gomez classification. Both groups were evaluated for measles complications like pneumonia, diarrhoea, encephalitis, corneal ulceration, thrombocytopenia, otitis media and myocarditis by detailed history and complete physical examination, and statistically analysed. Results: In the studied patients, 75 were males and 45 were females. Mean age was 23 months. Fifty-nine (49.2%) patients were well-nourished and 61 (50.8%) were undernourished. Fifty-two (43.3%) patients were having pneumonia. Fifty-three (44.2%) patients were having diarrhoea. Twenty-six (21.7%) patients were having encephalitis. Corneal ulceration was found in 9 (7.5%) patients. Thrombocytopenia and otitis media was present in 1 patient in each group. Fourteen patients expired. Conclusion: Measles is a global epidemic problem having many serious complications, including pneumonia, diarrhoea, encephalitis, corneal ulcerations etc. Moreover these complications are more frequent in under nourished children. Efforts should be made to improve the nutritional status of the children and to eradicate this disease by effective vaccination. Keywords: Measles, well-nourished, under-nourished, pneumonia, encephalitis, diarrhoea, complications, vaccination, mortality